Life at the Margins: Chronicles from Inner Areas of Calabria - Musolino, Elena (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
The logics that govern contemporary societies and economies produce increasing forms of marginalisation and new types of peripheral territories (Harvey 2003). The phenomena of polarisation of economic activities generate social changes of enormous magnitude that are reflected in complex and differentiated forms on local territories. Inner areas, as they have been identified within the innovative public policy dealing with development and territorial cohesion, are peripheral areas, distant from the offer of essential services of mobility, health and education, often characterised by strong depopulation, but at the same time they are custodians of an enormous environmental and cultural heritage (Partnership Agreement, 2013). Through the territorialist prism, inner areas will be read in order to describe the opportunity to define settlement models that can ensure the lasting sustainability of contemporary places, taking communities and their relationships with their environments as reference points. For the sustainable planning of inner areas, this paper will explore the present narratives to strengthen a systemic vision worthy of a possible future.